If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 + 2x + 5 = 90 Reorder the terms: -2 + 5 + 3x + 2x = 90 Combine like terms: -2 + 5 = 3 3 + 3x + 2x = 90 Combine like terms: 3x + 2x = 5x 3 + 5x = 90 Solving 3 + 5x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5x = 90 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 90 + -3 5x = 90 + -3 Combine like terms: 90 + -3 = 87 5x = 87 Divide each side by '5'. x = 17.4 Simplifying x = 17.4
| 7*-119/3/3 | | (2x^3/3y^2)3 | | 50x+75y=575 | | 3y+5x=x+9 | | 4x^3+30x^2+36x= | | f(2)=x^2+2x-1 | | 10y^4+2y^2= | | X/-6+8=12 | | 6(-7d+9)-2= | | 5-3z=2 | | 9(x-4)=9-33 | | -2(3x-3)=4x-9 | | 2-4x=-6 | | 4n-24m= | | 225x+4=0 | | ln(x-1)-ln(2x+3)=1 | | f(x)=6x^2-7x+18 | | 7-3d=-18 | | 12+4m=-9 | | 45=6x-3 | | 9-2p=16 | | lx(x-1)-ln(2x+3)=1 | | 34=2x+3x+9 | | 4x+1.5y=6 | | ln(x-1)-ln(2x+3)=1/2 | | 6+5x-x=42 | | 3(2x+5)-8=1 | | d-38=14 | | -(5X-4Y-7)= | | 132-r=209 | | (5/x-3)+1=(30/x^2-9) | | -4-q=-7 |